Ecological trade-offs in the deep sea: ontogenetic migration and synchrony in the red snow crab, Chionoecetes japonicus (Decapoda: Oregoniidae) - Takeo Yamamoto; Akane Yoshikawa; Yuji Ueda; Katsuyuki Hamasaki (Aquatic Ecology, 2026)

Onnamides and a Novel Analogue, Onnamide G, as Potent Leishmanicidal Agents - Takahiro Jomori; Nanami Higa; Trianda Ayuning Tyas; Natsuki Matsuura; Yudai Ueda; Ayumi Suetake; Shin Miyazaki; Shuichi Watanabe; Sei Arizono; Yasuhiro Hayashi; Ko Yasumoto; Yuji Ise; et al. (Marine Biotechnology, 2025)
Leishmaniasis is a neglected tropical disease posing significant global health challenges. Given the limited effective treatment options and associated constraints, many patients are unable to complete therapy. In this study, we report the remarkable leishmanicidal activity of onnamides derived from the marine sponge Theonella sp. against the promastigote form of Leishmania major (IC 50 = 0.2–140 nM) and demonstrate their selectivity through cytotoxicity assessments on human hepatoma HepG2 cells. Structural-activity relationship (SAR) analyses were conducted using 6,7-dihydro-onnamide A and its analogs. Furthermore, we compared the action mechanisms of amphotericin B, the primary drug currently used for treatment, and the obtained onnamides. Based on biological evaluations and SAR studies, onnamides can be considered promising candidates for anti-leishmanial chemotherapy, warranting further investigation.

Effect of temperature on survival and development of early juvenile red snow crabs Chionoecetes japonicus (Decapoda: Oregoniidae) under laboratory conditions - Takeo Yamamoto; Yuji Ueda; Katsuyuki Hamasaki (Invertebrate Reproduction & Development, 2025)

Experimental investigation of nonisothermal interaction between Fe-Zr melt and stainless steel forming “metallic debris” in Fukushima Daiichi Nuclear Power Station - Ayumi Itoh; Tatsuya Kanno; Takayuki Iwama; Shigeru Ueda; Takumi Sato; Yuji Nagae (Annals of Nuclear Energy, 2025)

Road to extinction: Archival samples unveiled the process of inbreeding depression during artificial breeding in an almost extinct butterfly species - Naoyuki Nakahama; Tatsuro Konagaya; Shouhei Ueda; Norio Hirai; Masaya Yago; Yuki A. Yaida; Atushi Ushimaru; Yuji Isagi (Biological Conservation, 2024)

Paleoproterozoic to Cenozoic zircon U–Pb ages with Hf signatures from metamorphic rocks and granodiorite of Tokunoshima: constraints on the geotectonic subdivision of the Ryukyu island arc, Southwest Japan - Hiroshi Yamamoto; Kazuaki Okamoto; Sun-Lin Chung; Hao-Yang Lee; Yuji Mita; Shuro Ueda; Masaru Terabayashi (International Geology Review, 2022)

Effect of temperature on red snow crab Chionoecetes japonicus (Crustacea, Decapoda, Majoidea) larval survival, development, and growth under laboratory conditions - Takeo Yamamoto; Yuji Ueda; Katsuyuki Hamasaki (Invertebrate Reproduction & Development, 2021)

Genetic population structure and demographic history of a pelagic lumpsucker, Aptocyclus ventricosus - Takumi Okazaki; Duane E. Stevenson; Yoshiaki Kai; Yuji Ueda; Tomonori Hamatsu; Yoh Yamashita (Environmental Biology of Fishes, 2020)

Breeding biology of the Fan-tailed Gerygone Gerygone flavolateralis in relation to parasitism by the Shining Bronze-cuckoo Chalcites lucidus - Alfredo Attisano; Felix Thiel; Nozomu Sato; Yuji Okahisa; Diana Bolopo; Keita D. Tanaka; Ralph Kuehn; Roman Gula; Keisuke Ueda; Jörn Theuerkauf (Journal of Ornithology, 2019)

Material recycling in a sediment‐starved trench recorded in the Early Cretaceous Shiriya accretionary complex, Northeast Japan - Hayato Ueda; Sho Kimura; Takahiro Saito; Yumi Takano; Natsumi Iizuka; Yuji Orihashi (Island Arc, 2018)
Identifying and examining geological processes that have occurred in sediment‐starved trenches of ancient non‐accretionary subduction zones exposed on land are still challenging, because such style of subduction is believed to leave scarce rock records. Our new geological mapping, petrography of coarse clastic rocks, radiolarian and zircon U–Pb dating of the Shiriya accretionary complex in Northeast Japan suggest that the younger parts (Sr1 unit) of the complex formed in a sediment‐starved trench. The key observation is that debris derived from the inner trench slope directly overlies pelagic chert in many sections where trench turbidites are lacking. A significant mass of turbidites occurring in other sections are also considered to represent distal facies of the debrites from the adjacent inner trench slope, rather than normal trench‐fill turbidites directly supplied from the continental landmass. These recycled materials from the inner trench slope comprised an imbricate frontal accretionary wedge, together with pelagic siliceous deposits of ocean floor origin. This accretionary wedge of debrite origin suggests that mass wasting on inner slopes of sediment‐starved trenches does not always result in tectonic erosion (removal of materials from the upper plate), but results in material recycling to reconstruct a new frontal accretionary wedge. The spatial dimensions of the recycling cell may be one of the critical differences between accretionary and non‐accretionary margins. Recycled continental materials transported by turbidites from remote landmasses construct frontal wedges in accretionary margins, whereas mass wasting on adjacent slopes and re‐accretion at the trench recycle continental materials in non‐accretionary margins. The transition from an accretionary to non‐accretionary (i.e. sediment‐starved) trench detected in the Shiriya Complex potentially records tectonic response of the inner trench slope to increased friction along the subduction interface.

Moulting and growth in earlier and later moulters of adolescent male snow crabs ( Chionoecetes opilio ) (Brachyura: Majoidea) under laboratory conditions - Takeo Yamamoto; Tatsuya Yamada; Takahiro Kinoshita; Yuji Ueda; Atsushi Yamasaki; Katsuyuki Hamasaki (Invertebrate Reproduction & Development, 2018)

Enzymatic activities for lignin monomer intermediates highlight the biosynthetic pathway of syringyl monomers in Robinia pseudoacacia - Jun Shigeto; Yukie Ueda; Shinya Sasaki; Koki Fujita; Yuji Tsutsumi (Journal of Plant Research, 2017)

Genetic population structure of Crystallichthys matsushimae (Cottoidei: Liparidae) with comments on color variation - Akira Tohkairin; Yoshiaki Kai; Yuji Ueda; Tomonori Hamatsu; Masaki Ito; Tetsuji Nakabo (Ichthyological Research, 2016)

Molecular insights into geographic and morphological variation within the Eumicrotremus asperrimus species complex (Cottoidei: Cyclopteridae) - Yoshiaki Kai; Duane E. Stevenson; Yuji Ueda; Tomonori Hamatsu; Tetsuji Nakabo (Ichthyological Research, 2015)

Demographic histories of two deep-sea eelpouts, Lycodes japonicus and Lycodes ocellatus: paleoenvironmental implications of the western North Pacific deep waters - Kay Sakuma; Yuji Ueda; Masaki Ito; Shigeaki Kojima (Ichthyological Research, 2015)

Morphological divergence between two color morphotypes of Crystallichthys matsushimae (Cottoidei: Liparidae) - Akira Tohkairin; Yoshiaki Kai; Yuji Ueda; Tomonori Hamatsu; Masaki Ito; Tetsuji Nakabo (Ichthyological Research, 2015)

The DnaA N ‐terminal domain interacts with Hda to facilitate replicase clamp‐mediated inactivation of DnaA - Masayuki Su'etsugu; Yuji Harada; Kenji Keyamura; Chika Matsunaga; Kazutoshi Kasho; Yoshito Abe; Tadashi Ueda; Tsutomu Katayama (Environmental Microbiology, 2013)
Summary DnaA activity for replication initiation of the E scherichia coli chromosome is negatively regulated by feedback from the DNA ‐loaded form of the replicase clamp. In this process, called RIDA (regulatory inactivation of DnaA ), ATP ‐bound DnaA transiently assembles into a complex consisting of Hda and the DNA –clamp, which promotes inter‐ AAA + domain association between Hda and DnaA and stimulates hydrolysis of DnaA ‐bound ATP , producing inactive ADP – DnaA . Using a truncated DnaA mutant, we previously demonstrated that the DnaA N ‐terminal domain is involved in RIDA . However, the precise role of the N ‐terminal domain in RIDA has remained largely unclear. Here, we used an in vitro reconstituted system to demonstrate that the Asn ‐44 residue in the N ‐terminal domain of DnaA is crucial for RIDA but not for replication initiation. Moreover, an assay termed PDAX (pull‐down after cross‐linking) revealed an unstable interaction between a DnaA ‐ N 44 A mutant and Hda . In vivo , this mutant exhibited an increase in the cellular level of ATP ‐bound DnaA . These results establish a model in which interaction between DnaA Asn ‐44 and Hda stabilizes the association between the AAA + domains of DnaA and Hda to facilitate DnaA – ATP hydrolysis during RIDA .

Gourmand New Caledonian crows munch rare escargots by dropping - Keita D. Tanaka; Yuji Okahisa; Nozomu J. Sato; Jörn Theuerkauf; Keisuke Ueda (Journal of Ethology, 2013)

Value-per-recruit analysis of bighand thornyhead Sebastolobus macrochir caught off the Pacific coast of northern Honshu, Japan - Pavarot Noranarttragoon; Yuji Ueda; Tsutomu Hattori; Takashi Matsuishi (Fisheries Science, 2011)

Osteogenic Induction of Bone Marrow-Derived Stromal Cells on Simvastatin-Releasing, Biodegradable, Nano- to Microscale Fiber Scaffolds - Ryu Wadagaki; Daiki Mizuno; Aika Yamawaki-Ogata; Makoto Satake; Hiroaki Kaneko; Sumitaka Hagiwara; Noriyuki Yamamoto; Yuji Narita; Hideharu Hibi; Minoru Ueda (Annals of Biomedical Engineering, 2011)

Spatiotemporal variations in nutritional status and feeding habits of immature female bighand thornyhead Sebastolobus macrochir off the Pacific coast of northern Honshu, Japan - Tsutomu Hattori; Takehiro Okuda; Yoji Narimatsu; Yuji Ueda; Masaki Ito (Fisheries Science, 2009)

Estimation of terminal molting probability of snow crab Chionoecetes opilio using instar- and state-structured model in the waters off the Pacific coast of northern Japan - Yuji Ueda; Masaki Ito; Tsutomu Hattori; Yoji Narimatsu; Daiji Kitagawa (Fisheries Science, 2009)

Effects of transforming growth factor-beta 1 and ascorbic acid on differentiation of human bone-marrow-derived mesenchymal stem cells into smooth muscle cell lineage - Yuji Narita; Aika Yamawaki; Hideaki Kagami; Minoru Ueda; Yuichi Ueda (Cell and Tissue Research, 2008)

Annual changes in distribution depths of bighand thornyhead Sebastolobus macrochir off the Pacific coast of northern Honshu, Japan - Tsutomu HATTORI; Yoji NARIMATSU; Masaki ITO; Yuji UEDA; Daiji KITAGAWA (Fisheries Science, 2008)

Somatic growth and otolith microstructure of larval and juvenile pacific cod Gadus macrocephalus - Yoji Narimatsij; Tsutomu Hattori; Yuji Ueda; Hiroshi Matsuzaka; Masaru Shiogaki (Fisheries Science, 2007)

Growth changes in bighand thornyhead Sebastolobusmacrochir off the Pacific coast of northern Honshu, Japan - Tsutomu HATTORI; Yoji NARIMATSU; Masaki ITO; Yuji UEDA; Kunihiro FUJIWARA; Daiji KITAGAWA (Fisheries Science, 2007)

Weight-based yield per recruitment and spawning-biomass per recruitment analyses of Pacific cod Gadus macrocephalus off the Pacific coast of southern Hokkaido, Japan - Yuji UEDA; Takashi MATSUISHI (Fisheries Science, 2005)

Molecular detection and direct enumeration of methanogenic Archaea and methanotrophic Bacteria in domestic solid waste landfill soils - Ann-Cheng Chen; Kumiko Ueda; Yuji Sekiguchi; Akiyoshi Ohashi; Hideki Harada (Biotechnology Letters, 2003)

Improved productivity by reduction of the content of light-harvesting pigment in Chlamydomonas perigranulata - Yuji Nakajima; Mikio Tsuzuki; Ryohei Ueda (Journal of Applied Phycology, 2001)

The effect of reducing light-harvesting pigment on marine microalgal productivity - Yuji Nakajima; Ryohei Ueda (Journal of Applied Phycology, 2000)

Improvement of microalgal photosynthetic productivity by reducing the content of light harvesting pigment - Yuji Nakajima; Ryohei Ueda (Journal of Applied Phycology, 1999)

Reduced photoinhibition of a phycocyanin-deficient mutant of Synechocystis PCC 6714 - Yuji Nakajima; Mikio Tsuzuki; Ryohei Ueda (Journal of Applied Phycology, 1998)

Improvement of photosynthesis in dense microalgal suspension by reduction of light harvesting pigments - Yuji Nakajima; Ryohei Ueda (Journal of Applied Phycology, 1997)